Development of user interface agent in multimedia courseware / Mohamad Shukri Abdurrahman Zuhair - Abdurrahman Zuhair, Mohamad Shukri (2005)
Recent years have witnessed the birth of a new paradigm for learning environments: animated interface agents. These lifelike autonomous characters inhabit learning environments with students to create rich, face-to-face learning interactions. This opens up exciting new possibilities; for example, agents can demonstrate complex tasks, employ gesture to focus student's attention on the most significant aspect of the task at hand and express emotional responses to the tutorial situation. Animated interface agents offer great promise for broadening the bandwidth of tutorial communication and increasing learning environment's ability to engage and motivate students. This project develops an animated pedagogical interface agent for multimedia courseware entitles KOMSAS. The introduction of a pedagogical interface agent to KOMSAS courseware enables it to provide higher motivational support to the students and enhances their quality of learning.